In-situ observation of damage structure in Cu-Cr-Zr and Cu-Cr alloy during 1.25 MeV electron irradiation. (March 2022) - Hatakeyama, M.; Yamamoto, T.; Yasuda, K.; Matsumura, S.; Yasunaga, K.; Sato, K.
Highlights: In-situ observations of electron irradiation to copper alloys were carried out. Most of the Cr precipitate/matrix interfaces are neutral sink for point defects. A part of Cr precipitate/matrix interfaces with interstitial bias exist. 1-D migration of dislocation loop was observed in Cu–Cr alloy at RT. Abstract: The sink strengths of precipitate/matrix interfaces in Cu alloys, were investigated by performing in-situ observation of electron irradiation in high-voltage electron microscopy (HVEM). Fine black spot defects, which seemed to be dislocation loops were observed at irradiation temperature ranging between RT and 373 K in Cu–Cr–Zr, Cu–Cr and GlidCop Al–60 alloys with low number density. In Cu–Cr, loops formed on a part of precipitates interfaces. Hence, a part of precipitate/matrix interfaces is a sink with interstitial bias. Whereas, most of the interfaces are neutral sinks for point defects. In the case of Cu–Cr–Zr and GlidCop Al–60, black spots formed around dislocation, which were induced during two-step heat treatment. The results showed that the precipitate/matrix interface of Cr-rich precipitates in Cu alloys serve as a strong sink for point defects.